Structural Studies of Zno Nanostructures on Porous Silicon: Effect of Post-Annealing Temperature - Alvin Eswar, Kevin; Husairi Fadzillah Suhaimi, Mohd; Guliling, Muliyadi; Khusaimi, Zuraida; Rusop, Mohamad; Abdullah, Saifollah (International Journal of Engineering and Technology, 2018)
ZnO Nanostructures have been successfully deposited on of Porous silicon (PSi) via wet colloid chemical approach. PSi was prepared by electrochemical etching method. ZnO/PSi thin films were annealed in different temperature in the range of 300 °C to 700 °C. Surface morphology studies were conducted using field emission scanning microscopy (FESEM). Flower-like structures of ZnO were clearly seen at annealing temperature of 500 °C. The X-ray diffraction spectra (XRD) have been used to investigate the structural properties. There are three dominant peaks referred to plane (100), (002) and (101) indicates that ZnO has a polycrystalline hexagonal wurtzite structures. Plane (002) shows the highest intensities at annealing temperature of 500 °C. Based on plane (002) analysis, the sizes were in range of 30.78 nm to 55.18. In addition, it was found that the texture coefficient of plane (002) is stable compared to plane (100) and (101).